PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 MAPAT TUNGGUL SELATAN KABUPATEN PASAMAN - Anepa, Anepa; Harisman, Yulyanti; Lovia, Lita (Pendidikan Matematika, 2014)
ABSTRACTThis research is individual learning studentsâ is complicated so they ask to another studentsâ without care it true or false on mathematics concept that still low and studentsâ not interest in learning mathematics. This research was aimed at revealing whether the use of Team Assisted Individualization strategies could give a better effect on the studentsâ understanding on mathematics concept than the conventional one in class VIII SMPN 1 Mapat Tunggul Selatan. This was an experimental research which used random research design toward the subject. The instrument used in this research is a test in studentsâ understanding on mathematics concept. Based on the result of data analysis, it was revealed that the sample was distributed normally and had homogeny variant. Hypothesis test results obtained t=1,94 was bigger than ,Â  indicating that the hypothesis was accepted. So, it was concluded that the application of Team Assisted Individualization strategies could improve the studentsâ understanding on mathematics concept, and better than the conventional one.